A comprehensive overview of the alignment between platoon control approaches and clustering strategies - M. Nandhini; M. Mohamed Rabik (Green Energy and Intelligent Transportation)
Platoon formation focuses on effectively coordinating the speeds of vehicles within a group, with automatic speed adjustments for each vehicle to maintain a desired formation. The implementation of appropriate control techniques in platooning is crucial to achieve efficient vehicle coordination to facilitate seamless communication and synchronization among vehicles. The platoon functions as a cluster, where vehicles within the platoon are treated as nodes. This study presents an idea for implementing clustering strategies in a platoon with a focus on achieving string stability by decreasing disturbances and variations in vehicle speed and position. This also involves an in-depth analysis of clustering algorithms to identify the most suitable approach for integration into vehicle platooning, specifically for network analysis purposes. The investigation of various control techniques and clustering algorithms aims to optimize the performance and functionality of platooning systems contributing to the advancement of wireless-connected autonomous vehicles and their transformative potential in transportation.